Collpa Thermal Spa & Lodge Hotel Boutique Orientado al Turismo de Bienestar en el Valle del Alto Chancay - Calixto, Ruddy Richard (2014)
Collpa Thermal Spa & Lodge is a business plan spurred by the opening of a new market for tourism within Peru’s expanding middle class and the demand for new products for this market that can also contribute to community development. This article seeks to provide information to those who seek to start a quality and sustainable tourism venture. Sustainability principles refer to the environmental, economic, and socio-cultural aspects of tourism development, and a suitable balance must be established between these three dimensions to guarantee its long-term sustainability (Organización Mundial del Turismo, 2013).